P137 OUTCOME OF PATIENTS UNDERGOING ENDOSCOPIC MUCOSAL RESECTION FOR CANCER OF THE OESOPHAGUS FROM A SINGLE CENTRE. (23rd November 2019) - Chmelo, J; Milito, P; Madhavan, A; Griffin, S M; Wahed, S; Hayes, N; Immanuel, A; Phillips, A W
Abstract: Aim: To evaluate the outcomes patients undergoing endoscopic mucosal resection (EMR) as a therapeutic and or diagnostic treatment for oesophageal cancer. Background: Management of early oesophageal cancer usually involves major surgery (oesophagostomy) which has a reported morbidity of 50% and mortality of 3%. EMR is increasingly used as a treatment for patients with early (T1 N0) oesophageal cancer. It may also be employed as a diagnostic tool in those where previous biopsies have been insufficient in proving a cancer. Methods: A retrospective review of patients who underwent EMR with a curative intent for cancer of the oesophagus or oesophago-gastric junction (OGJ) at a single centre between October 2006 and February 2019 was conducted. Patients were included in the study if the EMR sample was positive for T1a or T1b cancer. Results: Overall 144 patients were identified who underwent 276 therapeutic or diagnostic procedures. 141 patients were diagnosed with adenocarcinoma and 3 patients with squamous cell cancer (SCC). T1a stage was confirmed for 120 patients with adenocarcinoma and one with SCC. 21 patients with adenocarcinoma and 2 with SCC were staged as T1b. 78 patients underwent EMR as their sole treatment for cancer- three year cancer related survival was 89% and 5 year 69%. A further 49 patients progressed to having surgery (gastrectomy (2), trans-thoracic oesophagectomy (47). Six (12%) were node positive. There was no mortality associated with EMR, however bleeding requiring intervention or readmission was observed after 29 procedures (11%) and perforation was seen after 3 procedures (1.1%). Conclusion: EMR is a safe procedure in the treatment of early oesophageal or OG junctional cancer. However survival may not be as high as expected in patients similarly staged but undergoing more radical treatment.